Intestinal Parasites among Patients attending General Central Public Health Laboratory in Erbil City-Iraq during 1998-2004 - Narmin Hamad; Rezan Ahmed (College of Education for Pure Sciences, 1970)
Abstract The data of general stool examination of the patients attending the general central public health laboratory in Erbil city were collected during years 1998-2004 to estimate and determine the percentage of infections with parasitic species by direct method. Out of 5768 stool samples, examined 1380 were infected with intestinal parasites 23.9%. Statistically, there were high significant differences between infections and each of studied years and distribution of the parasitic species in relation to the sexes of the patients. Highest infection rate was 42.4% in the year 1998, while the lowest was 5% in 2004, and the males were infected with intestinal parasites more than females which were 60.2% and 39.8% respectively. The following parasites were detected in the present study: Entamoeba histolytica and Entamoeba coli with infection rates 51.7%, 51.2% and 0.6%, 0.7% in males and females, respectively, and intestinal flagellates, Giardia lamblia and Trichomonas hominis 40.3%, 39.9% and 3.1%, 5.1% in males and females, respectively. Taenia saginata 0.4% in each of males and females and Hymenolepis nana 3.4% in males and 2% in females, Ascaris lumbricoides and Enterobius vermicularis 0.1%, 0.2%, and 0.4%, 0.5% in males and females, respectively. Only 57 cases with double infections were recorded. High percentages of pus cells, red blood cells and Monilia fungi were present in the infected stools with pathogenic intestinal parasites like E. histolytica, G. lamblia, T. saginata, H. nana, A. lumbricoides and E. vermicularis.